Griscelli Type 2 Syndrome and Hemophagocytic Lymphohistiocytosis: Sisters With the Same Mutation but Different Presentations. Issue 6 (August 2019) - Russ, Abigail; Mack, Joana; Green-Murphy, Audrey; Occidental, Michael; Mian, Amir
Abstract : Griscelli syndrome type 2 (GS2) is an autosomal recessive condition associated with the development of hemophagocytic lymphohistiocytosis. GS2 is caused by a gene mutation involving RAB27A, which affects a melanosome anchoring complex in melanocytes and releases cytolytic granules from T cells and natural killer cells. GS2 is known to have immunologic compromise and oculocutaneous albinism. We present the case of 2 sisters who had vastly different phenotypic presentations despite having the same genetic frameshift mutation in the RAB27A gene. Patient 1 presented with seizures and neurological compromise, whereas patient 2 presented with pancytopenia and diarrhea. Both patients developed hemophagocytic lymphohistiocytosis. Abstract : Supplemental Digital Content is available in the text.